100 Trillion Good Bacteria Living in the Human Body - Rockett, Paul; Ruffle, Mark (Chicago, Illinois Raintree, an imprint of Capstone Global Library, 2015)
"Find out all about the human body, including the millions of bacteria that live in and on us and help our body function healthily, our digestive system, bones and muscles, blood and heart, lungs and breathing, the size of our brain, and the number of hairs on our head"--
Keywords: Human physiology -- Juvenile literature; Human body -- Juvenile literature; Literature